The economic and social role of married women in the agricultural production system in the region of Muea–Cameroon - Takamo, Fomu Agnes (2019)
Married women play a vital economic and social role in the agricultural production system in Cameroon. These women are mostly involved in food crop production. This research attempts to examine the economic and social roles of married women in the agricultural production system in Muea and the challenges they face which serve as limiting factors to their livelihood. Also, it looks at reasons why despite the contribution of married women, the society does not recognize their important role. The study further addresses issues on how they can overcome these challenges. It further brings out the part the various institutions are playing such as the government, non-governmental organizations, common initiative groups and micro-finance institutions.